The Effect of Acupressure Therapy on Sleep Quality of Elderly in Work Area of Melintang Health Center, Pangkalpinang - Triana Indrayani; Maulidia Damayanti; Nurul Husnul Lail (Universitas STRADA Indonesia, 2021)
Sleep disorder is one of the most common complaints in elderly. Effective sleep time decreases which results in not having good sleep quality and various kinds of sleep complaints. On the other hand, sleep quality of elderly can be improved by using effective and safe non-pharmacological methods, one of which is acupressure therapy. This study was a pre-experimental study with a one group pretest-posttest design. Sample was 30 elderly people who met inclusion criteria. Wilcoxon test obtained P value (0.000) < (0.05); therefore, Ho was rejected. It means that there was an effect of acupressure therapy on sleep quality of elderly. There is an effect of acupressure therapy on sleep quality of elderly in work area of Melintang Health Center. Elderly people are expected to be able to apply acupressure therapy at home as a non-pharmacological method as an attempt to improve sleep quality